Structure analysis and enhancement of creep resistance and thermal properties of eutectic Sn-Ag lead free solder alloy by Ti and Cd - addition - Yassin, Amal Mohamed; Khalifa, Berlent Abd El Hamed; Ismail, Reda Afify (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Eutectic (Sn-3.5wt.%Ag) solder alloy is used in electronic circuits in which the creep property of the solder joints is essential for their applications. The study of creep, structure and thermal properties of three solder alloys (Sn-3.5wt.%Ag,Sn-3.5wt.%Ag-0.27wt.%Ti and Sn-3.5wt.Ag-0.27wt.%Cd) is characterized by the presence of (Ag3Sn-IMC) beside the phase (Î²-Sn). The microstructure parameters obtained from the X-ray analysis represented by, lattice parameters (a, c), the axial ratio (c/a), the residual strains (Î”a/a0, Î”c/c0) and peak height intensities (hkl) of some crystallographic planes are given. All parameters were found to be sensitive to the additions of (Ti or Cd), applied stresses and working temperatures in the range (298-373K).The crystallite size of the (211) reflection was found to increase from (61-132nm) with the additions and to decrease from (115-79nm) with the working temperatures. The morphological studies show a remarkable decrease in the size of (Î²-Sn) grains with the addition of (Cd) content which confirms the X-ray data. The obtained results show a decrease in melting temperature with the additions. The creep properties are notably improved by the addition of either (Ti) or (Cd). In order to reveal the creep characteristics such as stress exponent (n) and activation energy (Q), the tensile creep tests were performed within the temperature range (298-373K) at constant applied stress (17.27MPa). Based on the obtained stress exponents and activation energies, it is explained that the dominant deformation mechanism is dislocation climb over all temperature range.